The role of foreign direct investment in structural change in Ethiopia - Ezo Emako; Seid Nuru; Mesfin Menza (Cogent Business & Management, 2022)
The paper examines the effect of foreign direct investment (FDI) on the structural changes in Ethiopia using an ARDL model. The authors found both FDI and domestic investment to have a positive effect while trade openness and inflation to have a negative effect on structural change. However, government expenditure does not seem to have a significant effect. The study concludes that FDI is an important tool for Ethiopia to achieve its transformation agenda generally and to bring about structural changes in particular. To this end, the government needs to attract sufficient FDI and ensure that it is used efficiently by improving absorption capacity and enabling domestic firms to make links with foreign investors.
Keywords: 650; foreign direct investment; ARDL; Ethiopia; industrialization; Structural change